Divergence or Relevance in Advertisements: What Works in Emerging Markets? Evidence from Indian Consumers. Issue 4 (7th August 2020) - Billore, Aditya; Jayasimha, K. R.; Sadh, Ashish; Nambudiri, Ranjeet
Abstract: This study selects the context of emerging markets to examine the role of ad creativity dimensions (divergence and relevance) in shaping the attitude of consumers. Most of the existing studies exploring consumer perceived creativity and its dimensions are based on inputs from consumers in developed markets. Using an experimental design, we test the differential effect of divergence and relevance for Indian consumers. The results indicate that for consumers from emerging markets, the role of relevance, which is mostly undermined, is as effective as divergence. The mediating role of attitude toward advertisement was established in the relationship between consumer perceived creativity and brand attitude. The main effects of divergence and interaction effects of divergence and relevance were found to be significant in influencing the consumers' ad and brand attitude as well as motivation to process information. Ads high in creativity were found to result in a higher unaided product and brand recall. Ads high on divergence also resulted in increased consumers' intentions to share the ad, which may be considered as a higher potential of becoming viral. The overall findings suggest that standardized advertising in global markets may have limited effectiveness.